Meeting and Working with H.T. Engelhardt Jr.: An Inspiring Experience for a (once young) European Scholar - Schotsmans, Paul (Conatus - Journal of Philosophy, 2018)
The author – a European “companion” of H. T. Engelhardt during the two last decades of the 20th century – describes his meetings with and impressions of Tris Engelhardt. He clarifies how open mindedness was the main concern in their common activities.